Pengembangan E-LKPD Berbasis Kahoot terhadap Peningkatan Keterampilan Numerasi dan Hasil Belajar Matematika Siswa Kelas V di SD Negeri 1 Bukit Tempurung - Eka Imelda; Najmuddin Najmuddin; Maisura Maisura (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aimed to develop a Kahoot-based E-LKPD for geometry material and examine its validity, practicality, and effectiveness on numeracy skills and mathematics learning outcomes of fifth-grade students at SD Negeri 1 Bukit Tempurung. The development followed the ADDIE model involving 30 students. Data were collected through interviews, questionnaires, and tests, then analyzed descriptively and quantitatively using Paired Sample T-Test. Results showed material expert validation reached 89.33% and media expert 98%, both categorized as very valid. Effectiveness testing demonstrated significant improvement with average scores increasing from 50.8125 (pretest) to 91.2500 (posttest), with significance value 0.000 < 0.05. Practicality testing reached 97%, categorized as very practical. This study concludes that Kahoot-based E-LKPD is highly valid, practical, and effective in improving numeracy skills and geometry learning outcomes for fifth-grade elementary students.